Respuesta :
(A)6x+4x-6=24+9x
10x-6=24+9x
10x-9x=24+6
x=30. (only 1 solution)
(B)25-4x = 15-3x+10-x
25-4x = 5-4x
25-5 = 4x-4x
30 = 0 (No solution)
(C)4x+8 = 2x+7+2x-20
4x+8 = 4x -13
4x-4x = -13-8
0 = -21 (No solution)
Answers:
A: one solution
B: one solution
C: one solution
Step-by-step explanations:
steps for solving a
step 1 collect the like terms
step 2 move variable to the left side and change its sign and move constant to the right side and change its sign
step 3 collect the like terms and add the numbers
steps for solving b
step 1 calculate the sum or difference and collect the like terms
step 2 factor out 4 from the expression
steps for solving c
step 1 eliminate the opposites and calculate the sum or difference